Music and displacement : diasporas, mobilities, and dislocations in Europe and beyond - Levi, Erik; Scheding, Florian, 1976- (Europea, 2010)
Music and Displacement offers an exploration of the interactions between music and displacement in theoretical and practical terms; a broadening of the remit of displacement and diaspora beyond Western art music; and a consideration of the topic within the contexts of music's socio-historical and philosophical circumstances, and to geographic and cultural pasts and presents.